Several Biomolecular Parameters as Prognostic, Therapeutic and Preventive Factors of Nasopharyngeal Carcinoma - Farhat Farhat (TALENTA PUBLISHER, 2020)
Introduction: Polymorphism of the enzyme in metabolyzing carcinogen such as CYP2E1 and GSTs are the genetic factor contributing for NPC. NPC also is related with several proteins that induce the growth and progression of tumor. Identification of the genetic variation and protein are beneficial for clinical use. Review: CYP2E1 polymorphisms are associated with increased activity and enzyme transcription, thereby increasing the activation of nitrosamines as carcinogens in NPC. In addition, polymorphism of GSTs as the phase II enzyme decrease the act to detoxify carcinogen and inhibit oxidative stress. Several studies showed the relation of those polymorphism with the risk factor of NPC. The protein expression in NPC was also studied by several researchers. Several proteins in NPC such as p38 MPAK, TNF-α, NF- κB, PPAR-gamma, LMP-1, VEGF, COX-2, and MMP-9 are related with tumor growth, prognosis and also help in treatment of NPC. Conclusion: Identifying GSTs and CYP2E1 polymorphism may be help in determining risk factor for NPC due to the association of those with increased susceptibility for NPC. Analyzing the protein expression by immunohistochemistry also help the clinician to identify the prognosis and considering therapy for NPC.